IMPROVEMENT OF PROFESSIONAL COMPETENCE OF LECTURERS IN EDUCATIONAL ORGANIZATION (Innovative professional education, 2024)
A quality of education for students depends on the quality of teaching and the professionalism of the lecturer. A professional competence is necessary component of the professionalism of the lecturer.Considering the process of improving the professionalism of lecturers, it is impossible to ignore the processes of advanced training of lecturers within the framework of professional educational organizations themselves.Pedagogical science and practice consider professional development inside the educational organization as avery important point in the system of continuous professional education. The purpose of work to improve the professional competence of the lecturer in the educational organization is to solve the problem of continuous, progressive, comprehensive development of the lecturer. the lecturer is providing with various, mobile forms and content of development, taking into account personal needs, experience, creative opportunities, experience, the ability to use advanced pedagogical experience taking into account the individual characteristics of each.
Keywords: professional competence, teaching staff, professional pre-higher education, development, networking